Synthesis and study of the chiral magnetic system EuIr2 P2 - Franco, Diego Gaspar (2021)
Chiral materials, where no improper symmetry operations such as inversion are present, are systems prone to the appearance of a skyrmion lattice. Recently it has been shown theoretically that not only ferromagnets (FMs) but also antiferromagnets (AFMs) can host such kind of phases. In this work we study a new candidate for AFM skyrmions, EuIr2P2, by means of magnetization and specific heat measurements on poly and single crystals. X-ray diffraction confirms a trigonal chiral crystal structure, where europium ions form helices along the c direction. In spite of predominantly FM interactions, Eu2+ ions order antiferromagnetically at TN1=5 K in what seems to be an incommensurate amplitude-modulated magnetic state where the moments are oriented mainly along the c direction. A second magnetic transition takes place at TN2=2.9 K, involving the ordering of an in-plane component of the Eu moment likely resulting in an equal-moment structure. Specific heat data show a tail above TN1. Accordingly the magnetic entropy at TN1 is strongly reduced in comparison to the expected Rln8 value. This evidences a significant amount of frustration. A simple analysis based on a Heisenberg model indicates that the observed properties imply the presence of several relevant interactions, with competing FM and AFM ones resulting in frustration. Thus EuIr2P2 is a new interesting magnetic system, where chirality and frustration might result in unconventional magnetic textures.